UMPSA students drive marine awareness through creative English SULAM project - Nur Syafawati, Sabuan; Hafizoah, Kassim; Fatimah, Ali (UMPSA, 2025)
PORT DICKSON, 10 June 2025 – The implementation of the Service Learning Malaysia – University for Society (SULAM) initiative under the supervision of the Centre for Modern Languages (CML) through the project Public Service Announcement Videos of Ornamental Fish for Global Engagement was successfully carried out in close collaboration with the Port Dickson Ornamental Fish Centre. A total of 29 students from the Faculty of Civil Engineering Technology, pursuing the Bachelor of Building Construction Technology with Honours and enrolled in the Essential English course (ULE1352), took part in the project. They were guided and mentored by several staff members from the English Language Division, including senior lecturers and senior English language instructors such as Dr. Fatimah Ali, Associate Professor Dr. Hafizoah Kassim, Nur Syafawati Sabuan, Arulselvi Uthayakumaran, Norsuhardiliana Sahar, and Aisyah Hanum Abu Bakar.